From design to clinic: Engineered peptide nanomaterials for cancer immunotherapy - Du, Jing-Jing; Su, Zhenhong; Yu, Haoyi; Qin, Sanhai; Wang, Dongyuan (Frontiers in Chemistry, 2023)
Immunotherapy has revolutionized the field of cancer therapy. Nanomaterials can further improve the efficacy and safety of immunotherapy because of their tunability and multifunctionality. Owing to the natural biocompatibility, diverse design, and dynamic self-assembly, peptide based nanomaterials hold great potential as immunotherapeutic agents for many malignant cancers with good immune response and safety. Over the past several decades, peptides have been developed as tumor antigens, effective antigen delivery carriers or self-assembling adjuvants for cancer immunotherapy. In this review, we give a brief introduction of peptide based nanomaterials for cancer immunotherapy used as antigens, carriers and adjuvants and their current clinical applications. Overall, this review can facilitate further knowledge and understanding of peptide based nanomaterials for cancer immunotherapy, and may pave the way for the design of safe and efficient methods for future vaccines or immunotherapies.